Evaluation of the rabbit as a model for Chagas disease - II: histopathologic studies of the heart, digestive tract and skeletal muscle - Arnaldo Moreira da Silva; Luiz Eduardo Ramirez; Marlene Vargas; Edmundo Chapadeiro; Zigman Brener (Memorias do Instituto Oswaldo Cruz, 1996)
In order to investigate the value of the rabbit as an experimental model for Chagas' disease, seventy one animals were inoculated with different Trypanosoma cruzi strains and routes. The rabbits were submitted to necropsy in acute (earlier than three months of infection), recent chronic (three to six months) and late chronic (later than six months) phases. Myocarditis, generally focal and endomysial, occurred in 94.1%, 66.7% and 70.8% of the infected rabbits respectively in the acute, recent chronic and late chronic phases. The myocardial inflammatory exudate was composed by mononuclear cells, and also polymorphonuclear cells in the acute phase. In most cases of the late chronic phase, the myocarditis was similar to that described in the indeterminate form of human chagasic patients. Initial fibrosis occurred in the three phases but was more severe and frequent in the early chronic. Advanced fibrosis occurred only in the late chronic phase. Tissue parasites occurred only in the acute phase. The digestive tract and skeletal muscles showed mild and occasional lesions. Our data indicate that experimentally infected chagasic rabbits repeat some lesions similar to that of humans chagasic patients, specially that of the indeterminate form. So, it may be a useful, however not an ideal, model.